KEPRIBADIAN MELALUI PARTISIPASI ANGGARAN MEMPENGARUHI KESENJANGAN ANGGARAN (Studi Perilaku Eksekutif Dalam Perencanaan Anggaran 11 Kabupaten/Kota di Provinsi Riau) - Handayani, Ririn (Journal of Accounting and Strategic Finance, 2009)
The target population of this research  is the entire  structural  officers in 11  regencies/cities of Riau Province. Accessible population is entire  structural  officers in 4 technical   boards, which is   Regional Income Board (Dipenda),  regional Development Board (Bappeda), Regional Infrastructure and Settlement Board (Kimpraswill) and Regional Secretary  .Applying   stratified random sampling, total sampling is   140, out of135  returned questionnaires, 124 is good for the purpose of analysis. Structrual Equation Modelling (SEM) with AMOS  software  6 version  is used to examine the relationship among variables. Based on data analysis it is  found  intentional budgetary slack  conducted  by regional government in  di  11  regencies/cities of Riau Province.  The finding  is also supported  by  sistematic variance  of  financial statement  of each respective regencies/cities. Several   results also generate ; first, personality does not influence budgetary slack. Personality  of decision makers  must be represenative in the form of  budget particiaptory to influence budgetary slack.This research  has several limitation as  it is only  conducted  in executive board  located  in  11   regencies/cities of Riau Province  as  budget planners. In fact,  budget decision also involves regional house of representative or  Dewan Perwakilan Rakyat Daerah (DPRD) of  Riau   regencies/cities  as  agency that verify and control budgettting process.   Keywords:  personality, budget participatory, and budgetary slack